(3GdaQGFV GdTgGHjIs - (3eMeO Hf CMeO Hf eMehOs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi NjQ GdHQjI Cfj YedJ aj GdaQGFV CUdG eNJUQG jgOj MaXg hageg s
(3BNQgG (B:s
(3aUd (B: (3aGdeGd cdg dHjJ GdeGd CbGQH GdejJ aGde jcf BNQ GdhQKI hdG jQK eY GdBNQ Ydi eG TQWhG hgh Ydi Cf jJhGQK Ch jQK CMOgeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2 / 1520s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdaQGFVs